Identification and functional activity of a staphylocoagulase type XI variant originating from staphylococcal food poisoning isolates. (25th July 2016) - Suzuki, Y.; Matsushita, S.; Kubota, H.; Kobayashi, M.; Murauchi, K.; Higuchi, Y.; Kato, R.; Hirai, A.; Sadamasu, K.
Abstract: Staphylocoagulase, an extracellular protein secreted by Staphylococcus aureus, has been used as an epidemiological marker. At least 12 serotypes and 24 genotypes subdivided on the basis of nucleotide sequence have been reported to date. In this study, we identified a novel staphylocoagulase nucleotide sequence, coa310, from staphylococcal food poisoning isolates that had the ability to coagulate plasma, but could not be typed using the conventional method. The protein encoded by coa310 contained the six fundamental conserved domains of staphylocoagulase. The full‐length nucleotide sequence of coa310 shared the highest similarity (77·5%) with that of staphylocoagulase‐type (SCT) XIa. The sequence of the D1 region, which would be responsible for the determination of SCT, shared the highest similarity (91·8%) with that of SCT XIa. These results suggest that coa310 is a novel variant of SCT XI. Moreover, we demonstrated that coa310 encodes a functioning coagulase, by confirming the coagulating activity of the recombinant protein expressed from coa310. This is the first study to directly demonstrate that Coa310, a putative SCT XI, has coagulating activity. These findings may be useful for the improvement of the staphylocoagulase‐typing method, including serotyping and genotyping. Significance and Impact of the Study: This is the first study to identify a novel variant of staphylocoagulase type XI based on its nucleotide sequence and to demonstrate coagulating activity in the variant using a recombinant protein. Elucidation of the variety of staphylocoagulases will provide suggestions for further improvement of the staphylocoagulase‐typing method and contribute to our understanding of the epidemiologic characterization of Staphylococcus aureus . Abstract : Significance and Impact of the Study: This is the first study to identify a novel variant of staphylocoagulase type XI based on its nucleotide sequence and to demonstrate coagulating activity in the variant using a recombinant protein. Elucidation of the variety of staphylocoagulases will provide suggestions for further improvement of the staphylocoagulase‐typing method and contribute to our understanding of the epidemiologic characterization of Staphylococcus aureus .